Trends in multidrug-resistant tuberculosis - Dias-Baptista, I. M. F.; Uso, S. M. R. S.; Marcondes-Machado, J. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2008)
Multidrug-resistant tuberculosis (MDR-TB) is an increasing global problem. The extent and burden of MDR-TB varies significantly from country to country and region to region. Globally, about three per cent of all newly diagnosed patients have MDR-TB and the proportion is higher in patients who had previously received anti-tuberculosis (anti-TB) treatment reflecting the failure of programs designed to ensure complete cure of patients with tuberculosis. The management of MDR-TB is a challenge that should be undertaken by experienced clinicians at centers equipped with reliable laboratory services and implementation of DOTS-Plus strategy.
Keywords: tuberculosis; MDR-TB; XDR-TB; DOTS; DOTS-Plus